2016
DOI: 10.1097/rct.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Voxel-Based Morphometric Study of Age- and Sex-Related Changes in Gray Matter Volume in the Normal Aging Brain

Abstract: Significant age-related differences are present in gray matter volume across multiple brain regions during aging. The VPM approach may provide an emerging paradigm in the normal aging brain that may help differentiate underlying normal neurobiological aging changes of specific brain regions from neurodegenerative impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Several studies demonstrate a reduction of gray matter volume during aging [78][79][80][81][82][83][84] . More specifically, the volume of gray matter in the cortex and the cerebellum of older individuals is 18% and 13% smaller, respectively, than those of their younger counterparts 81 .…”
Section: Brain Modifications During Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrate a reduction of gray matter volume during aging [78][79][80][81][82][83][84] . More specifically, the volume of gray matter in the cortex and the cerebellum of older individuals is 18% and 13% smaller, respectively, than those of their younger counterparts 81 .…”
Section: Brain Modifications During Agingmentioning
confidence: 99%
“…More specifically, the volume of gray matter in the cortex and the cerebellum of older individuals is 18% and 13% smaller, respectively, than those of their younger counterparts 81 . There is also a significant loss of gray matter in the frontal, limbic, temporal, and parietal lobes but not in the occipital lobe 78,83 . Similarly, studies have also indicated that there is a decrease of white matter volume in the brains of older individuals 81,[85][86][87] .…”
Section: Brain Modifications During Agingmentioning
confidence: 99%
“…Potential contributors to GCA include age, WMH associated with CVD, and AD . Many studies have shown that the severity of GCA is associated with increased age . Resnick et al showed no detectable GCA over 1 year, but reported 1.5 cm 3 increase in ventricular volume over the same period in cross‐sectional data analyses .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, atrophy of the hippocampus has been found to correlate strongly with the severity of Alzheimer's disease, as determined by pathology at autopsy. Accurate quantification of the region-specific effects of aging is important for establishing a structural paradigm to identify age-related regional cortical changes and disease-specific regional cortical volume changes such as those that occur in Alzheimer's disease ( 11 ) . However, in the clinical setting, quantitative volumetric analysis of the brain is not always possible, because of financial constraints (especially in public health care systems), poor MRI technique, or limited operator knowledge for quality evaluation of the automated results.…”
Section: Introductionmentioning
confidence: 99%